Analysis Of Influencing Factors Poverty in East Nusa Tenggara Province 2016 – 2020 - Anggara, Dhitya; Utomo, Yuni Prihadi (Perpustakaan dan Penerbitan Unismuh Makassar, 2023)
The destitution rate in the East Nusa Tenggara District overall is still high, still over the public neediness level. This study means to analyze the factors that influence the System/City Destitution Level in the East Nusa Tenggara Locale in 2016-2020. Board information relapse examination is the examination utilized in this review. The free factors utilized in this study were the Human Advancement Record, Area The lowest pay permitted by law, Labor supply, Government Consumptions, and Training Level; while the reliant variable utilized is the Neediness Level. The information utilized is information from 22 rules/urban communities in East Nusa Tenggara Region in 2016-2020. The outcomes showed that the best evaluation model was the Fixed Effect Model (FEM). The model exists, with a coefficient (R2) of 0.998260. Labor and Government Consumptions were found to adversely affect the Destitution Level in the Regime/City of East Nusa Tenggara Territory in 2016-2020, while the Human Improvement File, Locale The lowest pay permitted by law, and Training Level factors affected the Neediness Level.